2009
DOI: 10.2478/s11756-009-0134-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of antiapoptotic protein survivin in malignant melanoma

Abstract: Abstract:We examined the expression of potential tumor marker survivin by immunohistochemical staining using antisurvivin antibody (DAKO, Clone 12C4) in a panel of 25 malignant melanomas. In each section, we assessed the percentage of positively stained tumor cells, the intensity of staining and its subcellular localization. Survivin was present in 23 out of 25 cases (92%). Nuclear staining was found in 2 of these 23 cases (8.7%) only, while cytoplasmic staining only was seen in 3 of them (13%). The combined n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Similarly, a high cytoplasmic to nuclear ratio of survivin was associated with an improved overall survival and, conversely, an increased nuclear to cytoplasmic survivin ratio was correlated with an unfavorable overall survival. Both of our previous studies [16,17] and recent results also demonstrated that nuclear and combined nuclear and cytoplasmic survivin reaction are associated with worse prognostic parameters, it is not a case of solely cytoplasmic positivity. It follows that different subcellular survivin compartmentalization has distinct functions.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similarly, a high cytoplasmic to nuclear ratio of survivin was associated with an improved overall survival and, conversely, an increased nuclear to cytoplasmic survivin ratio was correlated with an unfavorable overall survival. Both of our previous studies [16,17] and recent results also demonstrated that nuclear and combined nuclear and cytoplasmic survivin reaction are associated with worse prognostic parameters, it is not a case of solely cytoplasmic positivity. It follows that different subcellular survivin compartmentalization has distinct functions.…”
Section: Discussionsupporting
confidence: 53%
“…Review of literature shows that the location of survivin expression is still a matter of discussion [13]. As described previously, there are three patterns of survivin immunohistochemical positivity in malignant cells: nuclear, cytoplasmic and combined (nucleus and cytoplasm) [14,15,16,17]. However, the reason for subcellular compartmentalization of survivin in neoplastic tissues is not yet fully understood.…”
mentioning
confidence: 99%
“…It was found to be the fourth most highly expressed transcript in common cancers [6]. Therefore, survivin is currently undergoing intense research as a potential tumor biomarker [6,7,8,9]. In addition, several studies dealt with the prognostic significance of survivin [10,11,12].…”
mentioning
confidence: 99%
“…Contrary, all the patients with pT4a and pT4b tumors had strong local expression in numerous tumor cells, significantly higher than other histological stages. A significant correlation of survivin expression with histologic grade and stage was reported not only in melanoma 21 but also in tumor samples of the patients with endometrial carcinoma 22 , ovarian carcinoma 23 , hepatocellular carcinoma 24 and breast cancer 25,26 .…”
Section: Discussionmentioning
confidence: 95%